From first visit to forever fans: crafting customer loyalty in glamping through experience quality and engagement - Raditha Hapsari; Ananda Sabil Hussein; Abdul Ghofar; Mohd Hafiz Hanafiah (Cogent Business & Management, 2024)
This study contains two primary research aims. The first objective is to investigate the structure, dimensions, and indicators of experience quality at glamping resorts. Additionally, the study aims to analyze the interconnections between experience quality, trust, satisfaction, engagement, and customer loyalty at glamping resorts in Indonesia. This study combines the customer relationship quality and experience-engagement models to answer the proposed objectives. The data for this study were collected from several glamping resorts in East Java, Indonesia, with a total of 452 participants. The research was carried out in two phases. In the initial phase, the data was analyzed using Exploratory Factor Analysis (EFA). The findings indicate that the quality of the glamping experience is a multi-dimensional construct consisting of service attributes, glamping attributes, and access quality. The study employed Partial Least Square (PLS) to examine the correlations between variables in the second stage. The results suggest that the quality of the glamping experience plays a significant role in shaping consumer satisfaction, trust, and engagement. Furthermore, this study demonstrates that satisfaction, trust, and engagement mediate the effects of the quality of glamping experiences on customer loyalty. Upon the completion of research objectives, this study contributes to both theoretical and practical contributions.
Keywords: 650; Glamping experience quality; customers loyalty; relationship quality; trust; engagement